Model atmospheres of sub-stellar mass objects - Hubeny, Ivan (OXFORD UNIV PRESS, 2017)
We present an outline of basic assumptions and governing structural equations describing atmospheres of sub-stellar mass objects, in particular the extrasolar giant planets and brown dwarfs. Although most of the presentation of the physical and numerical background is generic, details of the implementation pertain mostly to the code COOLTLUSTY. We also present a review of numerical approaches and computer codes devised to solve the structural equations, and make a critical evaluation of their efficiency and accuracy.